Effective Methods of Passing the Language Teaching Methodology for Schoolchildren - Bobomurodova Zeboxon Hamroyevna (Web of Journals Publishing, 2023)
This article analyzes the relevance of the science of the methodology of teaching the native language and the methods of effective teaching it to schoolchildren in an accessible form.
Keywords: methodology, methodology of teaching the native language, dictation, method of speech development, communicative method of teaching, audiolinguism, method of full response.